Turismo de observação de botos-cinza: implicações para a conservação de uma espécie ameaçada de extinção - Santos, Josivânia Emanuelly Azevedo dos (Universidade Federal Rural do Semi-Árido, 2019)
Guiana dolphin (Sotalia guianensis), a species threatened with extinction in the national territory, is one of the main attractions of the Coastal Wildlife Reserve of Tibau do Sul (REFAUTS). However, the adoption of inadequate practices, resulting from the absence of effective management, has compromised the sustainability of such tourism, making it a significant threat to the Guiana dolphin. Therefore, the objective of this study was to: (i) describe who are and what the drivers of tourist boats are thinking about dolphin watching, and (ii) evaluate, through video monitoring, the compliance of the Guiana dolphin watching, in relation to the Municipal Law nº 349/2007, instrument that regulates this activity in the REFAUTS. Data collection occurred between 2014 and 2018, totaling 40 days of sampling. In REFAUTS, the tour operators are predominantly young and have the Guiana dolphin watching as the main source of income. There is still little knowledge among these professionals about the environmental aspects of the REFAUTS, including Municipal Law nº 349/2007. However, these tour operators said that they recognize the importance of the following aspects: Guiana dolphin, protected marine environment, codes of conduct, inspection program and tourist tax for REFAUTS. The video monitoring technique from the beach was considered low-cost and effective to assess the compliance of Guiana dolphin watching in the REFAUTS. In general, Guiana dolphin watching showed low compliance with Municipal Law nº 349/2007, with the registration of at least one infraction in most of the tours monitored. The results of this study should subsidize a tourism planning and enable a better planning of conservation policies, ensuring the protection of Guiana dolphins in the REFAUTS
Keywords: Golfinho; Monitoramento; Praia de Pipa; Percepção ambiental; Turismo de observação de cetáceos; Dolphin; Monitoring; Pipa beach; Environmental perception; Dolphin watching; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE